2007
DOI: 10.1007/s00192-007-0523-5
|View full text |Cite
|
Sign up to set email alerts
|

Results 1 year after the Reemex system was applied for the treatment of stress urinary incontinence caused by intrinsic sphincter deficiency

Abstract: We present 1-year results obtained with Reemex for the cure of intrinsic sphincter deficiencies (ISDs). We recruited all patients with primary cases of stress urinary incontinence (SUI) due to an ISD (Valsalva leak-point pressure less than 60 cm or maximal urethral closure pressure less than 20 cm) who did not receive previous surgery. Thirty-eight patients were operated on. Postoperative pain was 3 (range, 1-5, visual analogue scale) at 24 h from surgery. Immediate regulation (the day after surgery) was neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…Th e Remeex tension-free readjustable tape (TRT) system (Neomedic) is an adjustable device allowing the suburethral tension to be altered at any time postoperatively to increase the success rate of incontinence surgery and to overcome the complications of over-tightening. Previous studies (Iglesias and Espuna 2003;Araco et al 2008) have shown a subjective cure of 90 -95% using this technique but the follow-up period is short term only and usually limited to 12 -24 months. Th is study describes our long-term 5-year experience of the device in refractory stress urinary incontinence (SUI).…”
Section: Introductionmentioning
confidence: 97%
“…Th e Remeex tension-free readjustable tape (TRT) system (Neomedic) is an adjustable device allowing the suburethral tension to be altered at any time postoperatively to increase the success rate of incontinence surgery and to overcome the complications of over-tightening. Previous studies (Iglesias and Espuna 2003;Araco et al 2008) have shown a subjective cure of 90 -95% using this technique but the follow-up period is short term only and usually limited to 12 -24 months. Th is study describes our long-term 5-year experience of the device in refractory stress urinary incontinence (SUI).…”
Section: Introductionmentioning
confidence: 97%
“…For these patients, compressive or readjustable devices are recommended at our institution. The Argus® adjustable bulbourethral sling.has demonstrated good results even after external beam radiation treatment (12), whereas the Reemex system showed success in patients with intrinsic sphincter deficiency in the mid-term (13).…”
Section: Discussionmentioning
confidence: 99%
“…These methods work more effectively in SUI patients who have ISD or DU and who therefore have a high possibility of developing urinary leakage or retention after surgery. One survey reported that of 38 patients with ISD who underwent the REMEEX surgery, all of the surgeries remained successful after 1 year [11]. According to another survey, 40.6% of patients with SUI who underwent TVA resolved their complications of urinary leakage or retention by adjustment of the tension [12].…”
Section: Discussionmentioning
confidence: 99%